Application of palm shell activated carbon filter as a medium of indoor air contaminant adsorbent for indoor air quality improvement - Zakaria@Jawahir, Supa'at (2018)
For decades, the inclusion of activated carbon (AC) adsorption technique through filtration has gained significant interest on improvement of indoor air quality (IAQ) by reducing level of pollutant. The interest of reseachers in palm shell AC (PSAC) keep increase owing to the fact that this material has superior characteristic as compared to commercial AC. However, the investigation of PSAC performance for air filtration are still limited and no research could be found on relating the effect of burner for carbonization on PSAC properties. Therefore, the current research was focused on producing PSAC by using new fabricated burner, exploring the effect of combination of physical and chemical activation towards PSAC properties and investigating of PSAC air filter performance used in Mechanical Ventilation Air Conditioning (MY AC) system. Preliminary studies began with IAQ monitoring in different building condition. The present data revealed that at certain situation, the buildings environment was below than satisfactory level and required mitigation plan by introducing new air filtration media in MY AC system. The best quality of charcoal was obtained by Horizontal burner with less fume formation during carbonization process compare to other design. The physical properties analysis of palm shell charcoal showed the carbonization time (CT) 2 hours gained better charcoal properties and highly recommended to continue into the activation process. After the activation process, PSAC physical+chemical shows significantly higher pore development, surface area and adsorption capacity compare to the other process. The lowest density and the highest porosity up to 0.4632 g/cm3 and 7.11 % was calculated while the highest Iodine number of 1091.05 mg/g and BET surface area of 713.7 m2/g was obtained respectively in PSAC physical+chemical. Meanwhile, microstructure and composition analysis shows that, PSAC physical+chemical fully produced honeycomb fonn of porosity and comprised of C, 0, K and Ca contents for high adsorption capacity. The improvement of IAQ in the buildings was achieved with the application of PSAC air filter which shows low concentration of CO2 with 302 ppm, CO with 0.4 ppm , TVOC with 0.1 ppm and PM 10 with 0.02mg/m3 respectively compare to the commercial filter.